Addiction Memory, Family Functioning, and Depression in Illicit Drug Users: Self-Esteem as a Mediator - Li Zeng; Xiaojun Zhou; Yuge Lei; Jiayan Chen (Behavioral Sciences, 2024)
Depression is a common issue among illicit drug users. However, the interaction between addiction memory, family functioning, and depressive symptoms remains insufficiently examined. This study investigates the relationship between addiction memory, family functioning, and depressive symptoms, with self-esteem serving as a mediator. A random sample of 600 illicit drug users from Hubei, China, was evaluated using the Addiction Memory Intensity Scale (AMIS), Family APGAR Index, Patient Health Questionnaire (PHQ-9), and Rosenberg Self-Esteem Scale (RSES). A factorial algorithm was used to parcel the AMIS, PHQ-9, and RSES items, and structural equation modeling was applied to examine the mediation effect. The model fit the data well (χ2/df = 2.248, CFI = 0.956, NNFI = 0.966, RMSEA = 0.046, SRMR = 0.040), with significant path coefficients (p < 0.05). Addiction memory was positively correlated with depression (β = 0.195, p < 0.001), while family functioning negatively correlated with depression (β = −0.113, p = 0.008). Both addiction memory and family functioning indirectly influenced depression through self-esteem, with mediating effects equal to 1.154 (95% CI: 0.106 to 0.209) and −0.097 (95% CI: −0.154 to −0.047). These findings suggest that interventions targeting addiction memory and family functioning may alleviate depressive symptoms by improving self-esteem among illicit drug users.